2008
DOI: 10.1007/s00706-008-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of chromium bis-acetylide complexes

Abstract: (R = Ph, SiMe 3 , SiEt 3 , C:C-SiMe 3 n = 0, 1) were prepared and characterised by NMR, cyclic voltammetry, EPR, magnetic measurements, and X-ray single-crystal diffraction studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that [(dmpe) 2 Cr II (C 2 R) 2 ] complexes can be prepared by addition of 2 equiv of LiC 2 R to [(dmpe) 2 CrCl 2 ]. , However, Berben demonstrated that a dinuclear Cr I dinitrogen-bridged acetylide complex could be synthesized by mixing [(dmpe) 2 CrCl 2 ] with stoichiometric LiC 2 SiMe 3 and excess n -butyllithium; the latter acts as a reducing agent. Nitrogen dissolved in the solvents cap and bridge the reduced Cr(dmpe) 2 (C 2 R) moieties.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that [(dmpe) 2 Cr II (C 2 R) 2 ] complexes can be prepared by addition of 2 equiv of LiC 2 R to [(dmpe) 2 CrCl 2 ]. , However, Berben demonstrated that a dinuclear Cr I dinitrogen-bridged acetylide complex could be synthesized by mixing [(dmpe) 2 CrCl 2 ] with stoichiometric LiC 2 SiMe 3 and excess n -butyllithium; the latter acts as a reducing agent. Nitrogen dissolved in the solvents cap and bridge the reduced Cr(dmpe) 2 (C 2 R) moieties.…”
Section: Resultsmentioning
confidence: 99%
“…In light of these applications we were curious as to the ability of 1 to serve as a synthon to form a new σ‐bond via a salt metathesis reaction with LiC 2 Ph. We reasoned this substrate a good choice to evaluate the electrophilic reactivity of 1 as lithium phenylacetylide is readily prepared, [57] phenlacetylide complexes of Cr are known to the crystallographic record, [58–69] and the steric demands of the square‐capping pentadentate NHC ought not prohibit access by the phenylacetylide anion. We observed no change to the paramagnetic 1 H NMR spectrum over the course of 24 hr upon charging a J‐young NMR tube with 1 and 1.2 equivalents of lithium phenylacetylide using THF‐d8 solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution reactions of the Cl 2 Cr(dmpe) 2 complex with lithium acetylides to form bis(acetylide) complexes were investigated earlier in our group, [38] however similar conditions could not be adopted for the synthesis of the monosubstituted alkyne complexes and the dinuclear butadiyne complexes. Hence, a different synthetic strategy was sought that involved the use of trimethylstannyl alkynyl reagents with the starting Cl 2 Cr(dmpe) 2 complex.…”
Section: Resultsmentioning
confidence: 99%
“…[38] X-ray Diffraction Studies: Single-crystal X-ray diffraction data were collected at 183(2) K with an Xcalibur diffractometer (Agilent Technologies, Ruby CCD detector) for compounds 2, 2[SnMe 3 -Cl 2 ] 2 , 8, and 10, and with a SuperNova Dual diffractometer (Agilent Technologies, Atlas CCD detector) for compound 9 using a single wavelength Enhance X-ray source with Mo-K α radiation (λ = 0.71073 Å). The cell was equipped with a Au working and Pt counter electrode, and a nonaqueous reference electrode.…”
Section: H Nmr and Varianmentioning
confidence: 99%